2003
DOI: 10.1590/s0102-76382003000300009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical prophylaxis secundary to cryptogenic stroke or transient ischemic attack in patients with patent foramen ovale

Abstract: Introduction: Prevention of recurrent cryptogenic strokes or transient ischemic attacks in adults with patent foramen ovale (PFO) represents a therapeutic challenge. Antithrombotic pharmacological treatment is widely used, but its indication is limited because of its significant complications.Objective: To demonstrate the efficacy of the surgical closure of patent foramen ovale (PFO) as prophylaxis secondary to cryptogenic strokes or transient ischemic attacks of undetermined origin.Method: In this study, 31 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Guffi [6] demonstrated the efficacy of the surgical closure of PFO as prophylaxis to prevent cryptogenic strokes. However, in Guffi's study, no patients were found to have thrombosis on the edges of the PFO, as was the case in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guffi [6] demonstrated the efficacy of the surgical closure of PFO as prophylaxis to prevent cryptogenic strokes. However, in Guffi's study, no patients were found to have thrombosis on the edges of the PFO, as was the case in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the diagnosis of paradoxical embolism is presumed [6] . Tests such as D-dimer, venous Doppler of lower limbs, and chest CTs are useful for the study of DVT and PE [5] , but when stroke is concurrent, brain CT and echocardiogram are mandatory [2] .…”
Section: Discussionmentioning
confidence: 99%